2013
DOI: 10.1177/216507991306100504
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Hospital Staff Nurses Working on-Call Hours

Abstract: When nurses work on-call hours, they have limited ability to control the hours they work. Nurses may be required to work extra hours and, if they are unable to detach from work during break time, can experience fatigue and sleep disturbances. Previous studies have not examined factors associated with on-call work. In this pilot study, the authors examined state regulatory, organizational, and personal factors related to nurse on-call hours. Data were collected from registered nurses working in hospitals in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Thus, early ERCP within 72 h may be helpful for decompressing the biliary obstruction, although our study demonstrated that urgent biliary intervention within 24 h would not lead to the additive benefit of reduced total hospital stay and complication rates. In particular, the cost-effectiveness of urgent ERCP should also be considered [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, early ERCP within 72 h may be helpful for decompressing the biliary obstruction, although our study demonstrated that urgent biliary intervention within 24 h would not lead to the additive benefit of reduced total hospital stay and complication rates. In particular, the cost-effectiveness of urgent ERCP should also be considered [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 Evidence found in research on the relationship between organizational characteristics and the work hours of other hospital professionals might warrant further research on their physician colleagues. 19 , 20 As healthcare resources are a type of public good, health authorities might assign different care responsibilities to healthcare providers in order to maximize the effectiveness of healthcare resources in regional planning, for example by assigning isolation and responding hospitals for communicable diseases, drug addiction treatment and alternative treatment institutions, and children’s preventive healthcare institutions.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Working a nursing job requiring on-call hours leads to overtime, and limits the ability for the nurse to control the number of hours worked, and the ability to detach from work leading to fatigue and sleep disturbances. [5] Kang et al [6] recommend that the effects of stress be evaluated by the use of biobehavioral methodologies beyond the use of self-reporting instruments.…”
Section: Introductionmentioning
confidence: 99%
“…[17] There are many reasons nurses choose to work 12-hour shifts, which is often to increase work-life balance, but at times at the expense of sleep. [5] Overtime has been a prevalent practice as the result of chronic understaffing and times of high census related to winter months. [14] Overtime can increase the number of incidents of needlestick injuries, musculoskeletal injuries, and illnesses.…”
Section: Introductionmentioning
confidence: 99%